2014
DOI: 10.5812/jjm.11136
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone Susceptibility and Detection of qnr and aac (6’)-Ib-cr Genes in Community Isolates of Klebsiella pneumoniae

Abstract: Background:Plasmid-mediated quinolone resistance genes (PMQR) have been shown to play not only an important role in quinolone resistance, but also resistance to other antibiotics, particularly β-lactams and aminoglycosides. These genes are mainly associated with clinical isolates of Enterobacteriaceae. However, detection of PMQR genes in the community isolates can increase the dissemination rate of resistance determinants among bacteria.Objectives:This study aimed to investigate quinolone resistance and distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…Another finding indicated that rates of resistance to imipenem were 5.7% among ESBL producing Klebsiella isolates. In a study in Karaj all K. pneumoniae isolates were susceptible to imipenem ( 34 ). Du et al ( 29 ) reported 3.3% resistance to imipenem among Klebsiella pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding indicated that rates of resistance to imipenem were 5.7% among ESBL producing Klebsiella isolates. In a study in Karaj all K. pneumoniae isolates were susceptible to imipenem ( 34 ). Du et al ( 29 ) reported 3.3% resistance to imipenem among Klebsiella pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Since the neighboring countries of Iran have a similar distribution of quinolone resistance genes studied in this survey, the geographical location can play a key role in spreading of these genes. Recent studies showed increase in the quinolone-resistant clinical isolates of E. coli and K. pneumoniae among hospitalized patients in Iran [22,23]. Much more investigations need to simplify the actual incidence rate of quinolones resistance encoding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Here we identified qnr A , B and S in ESBL-producing K. pneumonia. The incidence rate of 15.6 % qnr in Kuwait compared to other countries in Asia such as Iran (30.4 %) [ 20 ]. Thailand (34.6 %) [ 21 ], Malaysia (37 %) [ 22 ], India (67 %) [ 23 ] and Saudi Arabia (44 %) [ 24 ] is considerably lower.…”
Section: Discussionmentioning
confidence: 99%